Comparison of adjuvant gemcitabine and capecitabine with gemcitabine monotherapy in patients with resected pancreatic cancer (ESPAC-4): a multicentre, open-label, randomised, phase 3 trial - Neoptolemos, John P.; Hackert, Thilo; Büchler, Markus W. (The lancet, 2017)
The ESPAC-3 trial showed that adjuvant gemcitabine is the standard of care based on similar survival to and less toxicity than adjuvant 5-fluorouracil/folinic acid in patients with resected pancreatic cancer. Other clinical trials have shown better survival and tumour response with gemcitabine and capecitabine than with gemcitabine alone in advanced or metastatic pancreatic cancer. We aimed to determine the efficacy and safety of gemcitabine and capecitabine compared with gemcitabine monotherapy for resected pancreatic cancer.